Rapid pacing is an independent predictor for high implantation depth using self-expandable devices in TAVR. (14th October 2021) - Veulemans, V; Maier, O; Piayda, K; Berning, K L; Binneboessel, S; Polzin, A; Afzal, S; Dannenberg, L; Horn, P; Jung, C; Westenfeld, R; Kelm, M; et al.
Abstract: Background/Introduction: Optimizing valve implantation depth (ID) plays a crucial role in minimizing conduction disturbances and achieving optimal functional integrity. Until now, the impact of intraprocedural fast (FP) or rapid ventricular pacing (RP) on the implantation depth has not been investigated. Purpose: Therefore, we aimed to 1) evaluate the impact of different pacing maneuvers on ID, and 2) identify the independent predictors of deep ID. Methods: 562 TAVR patients with newer-generation self-expandable devices were retrospectively enrolled and further separated into patients undergoing TAVR under FP (n=331; 58.9%) and RP (n=231; 41.1%). The final ID was analyzed, and the underlying functional, anatomical, and procedural conditions were evaluated by univariate and multivariate analysis. Results: The highest ID was reached under RP in severe aortic valve calcification and valve size 26 mm. Multivariate analysis identified left ventricular outflow (LVOT) calcification (OR 0.56 [0.37–0.85], p=0.006*), a bicuspid valve (OR 0.34 [0.11–1.0], p=0.049*), valve size 26 mm (OR 0.47 [0.28–0.81], p=0.006*), and RP (OR 0.57 [0.37–0.87], p=0.010*) as independent and highly preventable predictors for deep valve deployment. Independent risk factors for deep ID were the use of a 34 mm device (OR 1.96 [1.22–3.15], p=0.005*) and mild aortic valve calcification (OR 1.62 [0.01–2.61], p=0.046*). In a model of protective factors, ID was significantly reduced with the number of protective criteria (0–2 criteria: −5.6±2.6 mm vs. 3–5 criteria: −4.5±2.0 mm; p<0.0001*). Conclusion: Data from this retrospective analysis indicate that RP is an independent predictor to reach a higher implantation depth using self-expandable devices. Funding Acknowledgement: Type of funding sources: None.